Klein Four-Group and Darboux Duality in Conformal Mechanics - Pliouchtchai, M; Inzunza-Melo, L (American Physical Society, 2019)
We study the Klein four-group (K4) symmetry of the time-dependent Schrödinger equation for the conformal mechanics model of de Alfaro-Fubini-Furlan (AFF) with confining harmonic potential and coupling constant g=ν(ν+1)≥-1/4. We show that it undergoes a complete or partial (at half-integer ν) breaking on eigenstates of the system, and is the automorphism of the osp(2,2) superconformal symmetry in super-extensions of the model by inducing a transformation between the exact and spontaneously broken phases of N=2 Poincaré supersymmetry. We exploit the K4 symmetry and its relation with the conformal symmetry to construct the dual Darboux transformations which generate spectrally shifted pairs of the rationally deformed AFF models. Two distinct pairs of intertwining operators originated from Darboux duality allow us to construct complete sets of the spectrum generating ladder operators that identify specific finite-gap structure of a deformed system and generate three distinct related versions of nonlinearly deformed sl(2,R) algebra as its symmetry. We show that at half-integer ν, the Jordan states associated with confluent Darboux transformations enter the construction, and the spectrum of rationally deformed AFF systems undergoes structural changes. © 2019 authors. Published by the American Physical Society.